Performance Analysis of The Qurrota A'yun Educational Foundation in Ponorogo Using Balanced Scorecard - Muawanah, Nanik Budiati; Parawiyati; Cahyaningsih, Diyah Sukanti; Gantari , Beatrice Phoebe (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This research aims to determine and analyze the performance of the Qurrota A'yun Education Foundation based on the Balanced Scorecard method. This research uses a mixed-methods approach. Interview techniques, documentation, and questionnaires were used to collect research data. This study shows the results in the form of the Qurrota A'yun Education Foundation in general, having increased performance and being in the good category with an average score of 1, with a high level of teacher/staff and student satisfaction. Specifically, the research results show that the Qurrota A'yun Education Foundation: 1) from a financial perspective has good performance because it has an average score of 2 after measuring using ROA, ROE, NPM, BOPO, Cash Ratio, and billing effectiveness; 2) from the perspective of students who perform less well because they have an average score of -1 after measuring using student retention, acquisition and profitability; 3) from an internal business process perspective, it has good performance with an average score of 1 after measuring using innovation and ratios; 4) from the growth and learning perspective, it has poor performance because it has an average score of -1 after measuring using retention, productivity, and teacher/staff training ratio.